Primary Localized Cutaneous Nodular Amyloidosis Following Local Trauma - Lee, Dong Yoon (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
Primary localized cutaneous nodular amyloidosis (nodular amyloidosis) is a rare and distinct type of amyloidosis, in which amyloid L deposition is limited to the skin and typically manifested as a tumefactive nodule on the acral sites. However, the definite cause of nodular amyloidosis is still unknown. Although it is relatively well known that the amyloid deposits in nodular amyloidosis originate from immunoglobulin light chains secreted by local plasma cells, traumatic injury to the skin has rarely been recognized as a triggering factor of nodular amyloidosis. Herein, we present a case of a 50-year-old male patient with primary localized cutaneous nodular amyloidosis, which occurred after local trauma, and discuss the relationship between traumatic damage and dermal amyloid L deposition.